Influence Of Perceptions Of Ease, Usefulness, And Security On The Decision To Use QRIS - Eka Sunarya, Regita Aulia; Prayitno Utomo, Langgeng (DAS CONFERENCE INTERNATIONAL SERIES, 2016)
Technology has significantly transformed payment systems, particularly through the adoption of financial technology (fintech) based on digital payments. One of the most prominent fintech innovations in Indonesia is the Quick Response Code Indonesian Standard (QRIS), introduced by Bank Indonesia as a unified national QR-based payment system. QRIS integrates various digital payment applications, enabling transactions to be conducted more efficiently, conveniently, and quickly. Despite the increasing adoption of QRIS, several challenges remain, especially related to users’ perceptions of ease of use, usefulness, and security. This study aims to examine the influence of perceived ease of use, perceived usefulness, and perceived security on students’ decisions to use QRIS as a digital payment method. The study employs a quantitative approach and adopts the Technology Acceptance Model (TAM) as its theoretical framework. Data were collected through questionnaires distributed to university students and analyzed using statistical testing. The results indicate that perceived ease of use, perceived usefulness, and perceived security have a significant effect on students’ decisions to use QRIS. Perceived ease of use encourages adoption because QRIS is easy to learn and operate. Perceived usefulness enhances students’ willingness to use QRIS due to its efficiency, time-saving benefits, and transactional flexibility. Meanwhile, perceived security plays a critical role in building trust, particularly in financial transactions involving personal and financial data. These findings suggest that the successful adoption of QRIS among students is not solely driven by technological advancement but also by users’ confidence and perceived safety. Therefore, strengthening system security, enhancing digital literacy, and increasing public awareness are essential strategies to promote sustainable use of QRIS in the digital economy era.